Pengaruh Variabel Makro Ekonomi Terhadap Nilai Aktiva Bersih (NAB) Reksadana Syariah di Indonesia - Choirum Miha; Nisful Laila (Universitas Airlangga, 2017)
This research aims to determine the influence of macroeconomic variables affect Net Asset Value of Islamic Mutual Fund partially and simultaneously in Indonesia. The research also uses multiple regression analysis technique. The sample used for this research is obtained from monthly statistic data of Otoritas Jasa Keuangan, statistic of Bank Indonesia, and statistic of Ministry of Energy and Mineral Resources which had been published online from January 2009 to November 2015. The result of this research shows that partially, the inflation affects NAV of Islamic Mutual Fund insignificantly, interest rate affects NAV of Islamic Mutual Fund insignificantly, currency exchange rate affects NAV of Islamic Mutual Fund insignificantly, money supply affects NAV of Islamic Mutual Fund significantly, and Indonesia Crude Price affects NAV of Islamic Mutual Fund significantly. Simultaneously, all exogenous variables affect NAV of Islamic Mutual Fund in Indonesia.